Reconceptualising Atrial Fibrillation Using Renewal Theory: A Novel Approach to the Assessment of Atrial Fibrillation Dynamics. Issue 2 (2021) - Quah, ing Xian; Dharmaprani, Dhani; Lahiri, Anandaroop; Tiver, Kathryn; Ganesan, Anand N
No abstract available